Drawing: the point of contact - Norwood, T (2018)
This thesis is a study of the point of contact between pencil and paper during certain acts of drawing. It comprises three elements. Firstly, five ‘drawings’ which together raise the central question of the thesis: what arrests me, in the manner of a Barthesian punctum, about the point of contact between pencil and paper (and their proxies) in these particular drawings? These drawings are in evidence through written accounts introducing each chapter, and they are: (1) a practice of ‘half-blind’ life drawing; (2) a line drawn around the internal perimeter of a house; (3) several voice recordings made while walking in the dark; (4) a biro line drawn across a bed sheet; (5) a row of ink blots at the foot of a page. Secondly, the present document, which shows the endeavour of answering this question. Thirdly, a display of artefacts left over from the five drawings and the writing, which pose a question at the close of the thesis: when the writing is completed, what is left of the drawings that set it going? The present document is undertaken ‘drawingly’: employing a methodology and form learned from the point of contact at its centre and developed as a mode of enquiry adequate to this punctum’s apparent resistance to being named or wholly analysed. Building upon Jean-Luc Nancy’s characterization of a working drawing as a search for form, Derrida’s description of the ‘aperspective’ of the drawing stylus, and Laura U. Marks’ analysis of haptic visuality, this methodology lies at the intersection between the blindness associated with drawing, the association of vision with knowledge, and the association of creative work with not knowing. It is characterized by moving forward with acute attentiveness and close proximity to the object under scrutiny; paying myopically close attention to associations when and where they arise; accepting and thematizing the fact—and the risk—that such a perspective restricts the view of an end-point, of the wider imaginative and critical landscape around, and indeed of a blind spot at the centre of the object; and heeding the prospect—and, again, the risk—of ‘surfacing’ from myopia into circumspect analysis. Like Nancy’s working drawings, the completed thesis is proposed as a working document that bears the marks of the search for form it constitutes. In these terms, the present document arrives at a description of the point of contact as a figure for the ultimately frustrated attempt to consummate or cancel out some experience that is felt to be excessive. Finally, the document itself is proposed as such a figure, a proposal that in turn revises the original assumption that the punctum is the point of contact in drawing, instead revealing this point of contact as a highly wrought description of some further object that remains unidentified and unconsummated, but somewhat changed by being described.